Bangladesh-India Relations: The Impact of Colonial History on Modern Bilateral Ties - Amin, Md. Ashraful; Fahim, Azizur Rahman; Islam, Md. Masbahul (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The research has explored the impact of colonial history on modern relations between Bangladesh and India. The resource has focused on how historical laser has shaped contemporary political, economic and socio-cultural dynamics.Using post-colonial and international relations theories, the study examines key aspects such as the Bengal Partition, colonial trade policies, and shared cultural legacies.The findings of this study have revealed the Bengal partition has created some territorial disputes like border enclaves and water-sharing conflicts which continue to influence diplomacy.Similarly, colonial trade policies fostered economic dependencies, contributing to current trade imbalances and resource-sharing tensions.However, by following the cultural and linguistic legacies in South Asia different collaborations through soft diplomacy like border markets (haats) and regional platforms such as SAARC have been created.Throughout this research data has been collected from different literature like relevant articles, policy papers etc. All of these papers fall under secondary data collection. By collecting those data qualitative data analysis has been done with thematic pattern's argument. From the literature review, a literature gap has been found. From this literature gap and following the research aim, the research question and hypothesis have been developed. The findings have satisfied the research question and found the hypothesis was true.Finally, some recommendations are offered for both Bangladesh and India as recommendations. The recommendations emphasize resolving border disputes, developing equitable trade agreements, and leveraging cultural ties for regional cooperation. This research will contribute to post-colonial studies and offer actionable insights for policymakers to address historical grievances, enhance diplomatic relations, and foster sustainable development in South Asia.